Values in the genre strategy of the contemporary novel (“Sweet Tooth” by Ian McEwan and "Picnic on Ice" by Andrei Kurkov) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article researches some number ways of realizing the system of values in the contemporary novel from the perspective of the postmodern play with genre strategies and narratives. It describes those peculiarities and techniques with the help of which the system of values in the text is constructed.
Keywords: intellectual novel; genre strategy; system of values